Access and awareness to formal and informal microcredit among small coconut farmers in Hagonoy, Davao del Sur - Gappi, Lourdes Faith A.; Soledad, Miguel D.
Poverty is one of the major problems in the Philippines today. In order to address this problem, microfinance services were created, which include microcredit. In Hagonoy, Davao del Sur, 70 small coconut farmers were interviewed to determine the significant factors affecting their awareness and access to microcredit services. It was found that small coconut farmers have higher chances of accessing microcredit from informal financial institutions. Majority of the small coconut farmers prefer to access informal microcredit since they find their arrangements more favorable and more convenient. In addition, farmers have a negative perception on formal financial institutions due to their loan requirements. Results of the Multinomial Logistic Regression showed that education and farming experience significantly influence the farmer's decision to access informal microcredit. This means than an increase in one unit of education and farming experience would increase the probability of small coconut farmers' access to informal microcredit. Meanwhile, household income is the only factor that affects the decision of accessing formal microcredit. Thus, an increase in one unit in the household income would also increase the chances of accessing formal microcredit. Therefore, the awareness and knowledge of coconut farmers on formal financial institutions should be improved since they offer better microcredit programs for small coconut farmers.
Thesis, Undergraduate (BS Agribusiness Economics)-- University of the Philippines, Mindanao